Scientific alternative approach in Diabetes-An overview - Garg, Munish; Garg, Chanchal (Pharmacognosy Reviews)
Several attempts have been made in search of a suitable formulation for diabetes mellitus all over the world. Although, allopathic treatment helps to control the disease to an extent but regular medication and constant medical supervision always leads to non patient compliance and compels them to look for alternative measures. Out of them, herbal drugs seem to be promising, as scientific analysis of several plants reveal that they possess enormous therapeutic capabilities that modern medicines is searching for. Moreover, due to affordability especially in developing countries where resources are meager and where the coverage by health service is limited, more and more researchers are now working in this direction. This paper provides a general account of dietary management, physical activity with main focus on scope of herbal drugs and a comprehensive analysis of plants with proven antidiabetic activity that may provide insights for future study and development of herbal drugs in modern scientific perspective.
Keywords: diabetes; dietary management; physical activity; antidiabetic plants